Surface Reconstruction: Noble Metals - Vasyl’yev, M.A.; Bondarchuk, A.B; Tinkov, V.A. (Успехи физики металлов, 2001)
The paper reviews the most important achievements in the study of the surface-reconstruction phase transition on the low-index single crystals of Pt, Ir, and Au. A number of methods very sensitive to the surface layers are used to study the stable and metastable structures of the (100), (110), and (111) faces. Detailed consideration of the kinetics, critical parameters, activation energy, and geometrical models for 2D-surface phase transitions are presented. Main theoretical results based on the Ising 2D-model, calculations of the free energy with an embedded-atom method, and equilibrium Monte Carlo simulations are also given. В обзоре рассмотрены последние достижения в исследовании реконструкционных фазовых превращений в поверхностных слоях монокристаллов Pt, Ir и Au. Приведены результаты, полученные с помощью различных поверхностно-чувствительных экспериментальных методов. Наиболее подробно рассмотрены вопросы, относящиеся к кинетике, энергии активации, геометрическим моделям, критическим параметрам 2D-фазовых превращений. Представлены также результаты теоретических исследований, основанных на 2D-модели Изинга, методе внедренного атома и моделировании методом Монте-Карло. В обзорі розглянуто останні досягнення в дослідженні реконструкційніх фазових перетворень в поверхневих шарах монокристалів Pt, Ir та Au. Наведено результати, які отримані за допомогою різних повехнево-чутливих експериментальних методів. Найбільш детально розглянуто питання, що відносяться до кінетики, енергії активації, геометричних моделей, критичних параметрів 2D-фазових перетворень. Представлено також результати теоретичних досліджень, що базовані на 2D-моделі Ізінга, методі зануреного атому та моделюванні за методом Монте-Карло.